Rare complication of a dialysis catheter insertion - Balasubramanian, Santhanakrishnan (Clin Kidney J, 2014)
Insertion of a dialysis catheter is a very common procedure in renal medicine, which is associated with one or more complications in ∼15% of patients. Central venous catheter vascular erosion is a rare but serious complication, the incidence appears to be between 0.4 and 1% which can be difficult to diagnose, leading to increased morbidity and mortality. We report a case of a persistent left-sided superior vena cava (PLSVC) and a possible central venous catheter vascular erosion following insertion of a left-sided internal jugular dialysis catheter. We discuss the mechanisms, diagnosis and measures to limit vascular erosion and also briefly discuss PLSVC.